Mini tracking device / Ahmad Faris Ahmad Nazri and Abdul Basar Mohd Fauzi - Ahmad Nazri, Ahmad Faris; Mohd Fauzi, Abdul Basar (2015)
Based on our project, we have discovered that people nowadays had a problem to find their missing item. Somehow they forgot where the item had been located before. Thus, we build and designed a tracker device that can help them to trace their lost item. This tracker device is divided into two parts which is a receiver and a transmitter. The receiver device will be clip together with the item and the transmitter will be hold by the owner. If the item such as key is lost with a receiver that have been clip on it, the owner can trace their item by switching ON the transmitter. So, this project developed a low cost mini tracking device that will give benefit to the people.